MUSE sneaks a peek at extreme ram-pressure stripping events – V. Towards a complete view of the galaxy cluster A1367. Issue 4 (9th February 2022) - Pedrini, Alex; Fossati, Matteo; Gavazzi, Giuseppe; Fumagalli, Michele; Boselli, Alessandro; Consolandi, Guido; Sun, Ming; Yagi, Masafumi; Yoshida, Michitoshi
ABSTRACT: We present an analysis of the kinematics and ionization conditions in a sample composed of seven star-forming galaxies undergoing ram-pressure stripping in the A1367 cluster, and the galaxy ESO137–001 in the Norma cluster. MUSE observations of two new galaxies in this sample, CGCG097–073 and CGCG097–079, are also presented. This sample is characterized by homogeneous integral field spectroscopy with MUSE and by a consistent selection based on the presence of ionized gas tails. The ratio [O i ]/H α is consistently elevated in the tails of these objects compared to what observed in unperturbed galaxy discs, an ubiquitous feature which we attribute to shocks or turbulent phenomena in the stripped gas. Compact star-forming regions are observed in only ≈ 50 per cent of the tails, implying that specific (currently unknown) conditions are needed to trigger star formation inside the stripped gas. Focusing on the interface regions between the interstellar and intracluster medium, we observe different line ratios that we associate to different stages of the stripping process, with galaxies at an early stage of perturbation showing more prominent signatures of elevated star formation. Our analysis, thus, demonstrates the power of a well selected and homogeneous sample to infer general properties arising from ram-pressure stripping inside local clusters.